Ceremoniał dyplomatyczny na dworze angielskim w negocjacjach z Rzecząpospolitą w XVII wieku - Maciejewski, Piotr (Acta Universitatis Lodziensis. Folia Historica, 2005)
The article is an attempt to depict the ceremony which existed within the courtly-diplomatic relationships between Poland and England in the limes of Elisabeth I, James I and Charles I, and to show its role. The paper is based on such sources as the accounts of legations to England by Pawel Działyński (1597), Jerzy Ossoliński (1621) and Jan Zawadzki (1633). Some inside information was taken from the accounts or private travel of Jakub Sobieski (1609). The ceremony at the English court, similarly as in other capital cities visited by our diplomats, was not only essential for the international relationships and enabled contacts between countries in general, but it also ensured achieving the most important thing in politics — the compromise. Besides that, it served harmonious coexistence and secured comfort in any actions. I here was on condition for that of course: both sides should properly receive the signals given (e.g. gestures, greetings, speeches, toasting, feasts, gifts and tokens, etc.). The only visible difference between the two sides would be the outside difference e.g. in clothing. The above can be proved by the fact that Polish diplomats, equipped with instructions, letters from the country and the knowledge gained, could easily manage the relationships with the royalty and high range English diplomats. Polish diplomats didn’t find it difficult to adjust to the local customs (with the exception of the unprecedented case of Działyński).